'A very exclusive experiment in communism': the radical origins of the Manhattan co-op. (February 2023) - Masterson, Jack T.
Abstract: Though it has long been the residence of choice for Manhattan's rich, the co-operative apartment building has an intellectual lineage that originates in pre-Marxian communitarian socialism. In the early nineteenth century, radical philosophers Charles Fourier and Robert Owen first theorized a multifamily dwelling owned in joint stock by its residents that could deliver economies of scale in the production and delivery of household necessities. Using previously untranslated French sources and archival material (New Harmony Working Men's Institute), this article demonstrates how early socialist ideas about housing, domestic labour and ownership evolved into the idea for the New York City co-operative apartment building.